Vulnerability and Valour: A Gendered Analysis of Everyday Life in the Dead Sea Scrolls Communities - Keady, Jessica M. (The Library of Second Temple Studies, 2017)
Cover -- Title -- Copyright Page -- Contents -- Acknowledgments -- Abbreviations -- Chapter 1 Introduction -- 1. Setting the Scene -- 2. Methods Used in This Book -- 3. Definition of Key Terminology -- 4. The Contents of This Book -- Chapter 2 The Debate about Purity and Impurity in the Dead Sea Scrolls -- 1. The Purpose of This Chapter -- 2. Dead Sea Scrolls Scholarship on the Role of Purity and the Perceptions of Women from 1947 to 1969 -- 3. Dead Sea Scrolls Scholarship on the Role of Purity and the Perceptions of Women from 1970 to 1989 -- 4. Dead Sea Scrolls Scholarship on the Role of Purity and the Perceptions of Women from 1990 to the Present -- 5. Summary -- Chapter 3 Purity and Impurity in the Dead Sea Scrolls: Masculinity, Embodiment and the Everyday as Methodological Tools -- 1. The Purpose of This Chapter -- 2. Masculinity Studies as a Methodological Tool -- 3. Towards an Embodied Methodology -- 4. Theorizing the Everyday -- 5. Summary: Moving Beyond the Abstract -- Chapter 4 Masculinity Studies and the Men of the Dead Sea Scrolls Communities -- 1. The Purpose of This Chapter -- 2. The Rule of the Community (in Its 1QS Form) and Masculinity -- 3. Masculinity, Purity and Warfare in the War Scroll (in Its 1QM Form) -- 4. Summary: Purity, Shame and Honour-The Constructions of Masculinist Ideologies in the Rule of the Community and the War Scroll -- Chapter 5 Thinking Beyond the Abstract: Towards an Embodied Reading of Purity in 4QDg (4Q272), 4QDa (4Q266) and 4QTohorot A (4Q274) -- 1. The Purpose of This Chapter -- 2. Men and Women in their Daily Lives: Towards a Reconsideration of Masculinity and Femininity in 4QD.